2022
DOI: 10.1038/s41598-022-20072-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular health with the risk of dementia in older adults

Abstract: It has been becoming important to identify modifiable risk factors to prevent dementia. We investigated the association of individual and combined cardiovascular health (CVH) on dementia risk in older adults. From the National Health Insurance Service of Korea-Senior database, 191,013 participants aged ≥ 65 years without prior dementia or cerebrovascular diseases who had check-ups between 2004 and 2012 were assessed. Participants were stratified into three groups according to the number of optimal levels of CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Regarding dementia subtypes, we observed that cardiovascular risk was associated with vascular dementia and Alzheimer’s disease, in line with previous studies [ 4 , 43 45 ]. The associations were stronger with vascular dementia; these are expected results because the main risk factors for vascular dementia are included in the REGICOR-Framingham score.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding dementia subtypes, we observed that cardiovascular risk was associated with vascular dementia and Alzheimer’s disease, in line with previous studies [ 4 , 43 45 ]. The associations were stronger with vascular dementia; these are expected results because the main risk factors for vascular dementia are included in the REGICOR-Framingham score.…”
Section: Discussionsupporting
confidence: 92%
“…The main strength of this study was the high external validity grounded on a large sample size and 15 years of follow-up, which is longer than that in previous studies [ 10 , 43 , 45 ]. Moreover, the analysis of electronic health records allows the study of real-life clinical conditions and precludes a selection bias due to low response rates or losses during follow-up, which could be common among people with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the projected cardiovascular risk for this particular patient population is underestimated. Across all three stratification techniques utilized, patients with VD exhibited a high cardiovascular risk, aligning with heightened mortality rates, including cardiovascular mortality (18)(19)(20). This study underscores the significance of validating the numerous risk equations employed for assessing cardiovascular risk in VD patients and modifying them to incorporate adjustments based on the Hachinski criteria or other pertinent instruments in comprehensive assessments within such patient cohorts.…”
Section: Bmimentioning
confidence: 76%
“…Accordingly, the observed decreasing risk of CV risk factors or diseases for incident dementia with increasing age might be due to the fact that our studied outcome was all-cause dementia and that the presence of multiple pathologies, rather than vascular dementia on its own, seems to be involved in the development as age increase. Fifth, we should have been taking in account the CV risk level in the risk prediction of dementia with longitudinal data since, the improvement of CV modifiable risk was associated with a reduction of dementia risk 51 53 . Finally, we did not take in account the impact of level adherence of CV medication.…”
Section: Discussionmentioning
confidence: 99%